Exploration of Belitung Taro Stems (Xanthosoma sagittifolium) as an Antidiabetic Candidate: An In Silico and In Vitro Approach - Rahmatulloh, Wahyu; Supriyanto, Sugeng; Saputra, Aditya Mahe; Rahma, Nabila Aulia (Chempublish Journal, 2026)
Diabetes mellitus is a global metabolic disorder characterized by chronic hyperglycemia. While conventional oral antidiabetics are effective, their long-term use is associated with adverse side effects, necessitating the search for safer alternatives from natural sources. Belitung taro (Xanthosoma sagittifolium) is a locally abundant tuber crop in Indonesia, but its stems are typically discarded as agricultural by-products despite their potential bioactive content. This study evaluated the antidiabetic potential of X. sagittifolium stem extract by investigating its α-amylase inhibitory activity through an integrative in silico and in vitro approach. In silico screening was performed on eight secondary metabolites from the CMAUP database, filtered based on Lipinski's Rule of Five and ADMET profiles using the pkCSM server. The lead compound, NPC141921, was docked into human pancreatic α-amylase (PDB ID: 2QV4) using AutoDock, validated by redocking acarbose. The ethanol extract was subjected to phytochemical screening and tested for α-amylase inhibition using the iodine-starch assay. NPC141921 showed a binding free energy of -6.13 kcal/mol, comparable to acarbose (-6.66 kcal/mol), forming stable hydrogen bonds with catalytic residues (ASP197, GLU233, ASP300) and substrate-binding residues (ARG195, HIS305). Phytochemical screening confirmed flavonoids, tannins, saponins, and steroids, supporting the in silico predictions. In vitro assays revealed an IC₅₀ of 5028 ppm for the stem extract versus 1953 ppm for acarbose. Although the crude extract showed lower potency due to matrix dilution effects, the findings confirm that X. sagittifolium stems contain bioactive metabolites capable of α-amylase inhibition, highlighting their potential as a natural ingredient for hyperglycemia management.